Men and Monotony: Fraternalism as a Managerial Strategy at the Ford Motor Company - Lewchuk, Wayne (The Journal of Economic History, 1993)
The introduction of mass production transformed many skilled tasks into repetitive and monotonous jobs. In industries such as automobiles, the workforce remained predominantly male despite contemporary assessments that women could efficiently do many of these jobs. This article explores why. It is argued that employers such as Ford concluded that the conversion of labor time into effort would be more difficult in a mixed-gender workforce. The paper shows how Ford developed a fraternalist labor strategy, a men's club, whose objective was to accommodate men to monotony and maximize labor productivity.